Novel Anti-tumor Strategy for Breast Cancer: Synergistic Role of Oleuropein with Paclitaxel Therapeutic in MCF-7 Cells - Yılmaz, Gamze; Özdemir, Filiz (Anti-Cancer Agents in Medicinal Chemistry, 2024)
Background: The side effects of conventional therapeutics pose a problem for cancer treatment. Recently, combination treatments with natural compounds have attracted attention regarding limiting the side effects of treatment. Oleuropein is a natural polyphenol in olives that has antioxidant and anticancer effects. Objectives: This study aimed to investigate the oxidative stress effect of a combination of Paclitaxel, a chemotherapeutic agent, and Oleuropein in the MCF-7 cell line. Methods: The xCELLigence RTCA method was used to determine the cytotoxic effects of Oleuropein and Paclitaxel in the MCF-7 cell line. The Total Oxidant and Total Antioxidant Status were analyzed using a kit. The Oxidative Stress Index was calculated by measuring Total Oxidant and Total Antioxidant states. The levels of superoxide dismutase, reduced glutathione and malondialdehyde, which are oxidative stress markers, were also measured by ELISA assay kit. Results: As a result of the measurement, IC50 doses of Oleuropein and Paclitaxel were determined as 230 μM and 7.5 μM, respectively. Different percentages of combination ratios were generated from the obtained IC50 values. The effect of oxidative stress was investigated at the combination rates of 10%, 20%, 30%, and 40% which were determined to be synergistic. In terms of the combined use of Oleuropein and Paclitaxel on oxidative stress, antioxidant defense increased, and Oxidative Stress Index levels decreased. Conclusion: These findings demonstrate that the doses administered to the Oleuropein+Paclitaxel combination group were lower than those administered to groups using one agent alone (e.g. Paclitaxel), the results of which reduce the possibility of administering toxic doses.
Keywords: oxidative stress